A Hybrid Application For Real-Time Air Quality Monitoring - Silva, Jorge (2020)
With the raising concerns for the environment, interest in monitoring air quality is likely to increase in the near future. However, most data comes from a limited number of government-owned sensors, which can only capture a small fraction of reality. Improving data coverage thus involves reducing the cost of sensors and make data widely available. For this, we will use a very high number of low-cost sensors as the basis for an air quality monitoring platform, capable of collecting, aggregating, storing and displaying data. This platform will use stream-based technologies capable of scaling for large numbers of sensors and users. The resulting NanoSen-AQM platform will provide vast amounts of air quality data to the public, with the aim of improving public health.